2013
DOI: 10.1111/ctr.12261
|View full text |Cite
|
Sign up to set email alerts
|

Donor pre‐treatment in clinical kidney transplantation: a critical appraisal

Abstract: Kidney transplantation represents one of the medical achievements of the 20th century. However, its continued success is limited by the increasing shortage of donor grafts. As a result, more kidney grafts from marginal donors are being considered for transplantation, with concomitantly more initial graft injury and limited organ and patient survival. This has led to an increased need for interventions aiming to optimize and preserve graft quality. Interventions within the donor may protect against ischemia/rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…1 The donor organ undergoes a number of injurious insults prior to, and during the early post-operative phase that are thought to contribute to the later development of chronic rejection. 2, 3 One such insult is ischemia reperfusion injury (IRI). 4 IRI is an unavoidable complication in the process of cardiac transplantation, with the donor heart rendered ischemic for prolonged periods prior to implantation into the recipient and subsequent reperfusion.…”
Section: Introductionmentioning
confidence: 99%
“…1 The donor organ undergoes a number of injurious insults prior to, and during the early post-operative phase that are thought to contribute to the later development of chronic rejection. 2, 3 One such insult is ischemia reperfusion injury (IRI). 4 IRI is an unavoidable complication in the process of cardiac transplantation, with the donor heart rendered ischemic for prolonged periods prior to implantation into the recipient and subsequent reperfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the establishment of institutional review boards and ethic committees with specialist transplantation expertise is advisable to determine the consent process subject to the risk of intervention and to decide whether the recipient needs to give informed consent . Additionally, a safety monitoring board is reasonable, as it can guard each study subject enrolled within the clinical trial .…”
Section: Ethical Issues Of Donor Researchmentioning
confidence: 99%
“…In line with the danger hypothesis, this would attenuate the vicious circle of injury and increased immunogenicity after transplantation . Experimental studies highlight the benefits of this approach, but well designed clinical trials studying donor pretreatment are sparse . Trials should ideally assess the results of kidney transplantation by hard outcome data such as patient and graft survival, but can also consider early parameters such as DGF, biopsy‐proven acute rejection (BPAR), and evolution of graft function.…”
Section: Introductionmentioning
confidence: 99%
“…DBD management includes the treatment of hypertension during the Cushing phenomenon, followed by cardiovascular support with treatment of hypotension [22], and maintenance of adequate intravascular volume (as sustained hypotension is observed in 53 % of brain dead children) [23], avoiding hydroxyethyl starch [24]. In 2009, Schnuelle et al suggested that hemodynamic support by dopamine could improve kidney graft function [25].…”
Section: Pediatric Organ Donors and Their Managementmentioning
confidence: 99%
“…In 2009, Schnuelle et al suggested that hemodynamic support by dopamine could improve kidney graft function [25]. Hormone replacement with methylprednisolone, vasopressin (as diabetes insipidus is observed in 78 % of DBD children) [23] and thyroid hormone (to reduce vasopressor requirement) [25] is a widely used therapy, but controversial in the USA [22,26]. Several studies were unable to find any major effects of donor management on graft quality.…”
Section: Pediatric Organ Donors and Their Managementmentioning
confidence: 99%